Erratum: Pengaruh Aktivitas Olahraga Terhadap Emotional Intelligence Siswa Sekolah Menengah Pertama - Nur Mahfuzah Agustin; Amung Ma’mun; Tite Juliantine (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.606 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.